Surgical Experience With Oesophagectomy For Carcinoma Oesophagus At Shree Birendra Hospital - Rajbhandari, Gambhir Lal (Medical Journal of Shree Birendra Hospital, 1999)
Surgical Experience With Oesophagectomy For Carcinoma Oesophagus At Shree Birendra Hospital